Innovative Ecosystems as a Hidden Growth Driver for Ukrainian Small and Medium-Sized Businesses and Public Governance: are there Ground for Renewed Confidence? - Anosov , Oleksii (Pressing Problems of Public Administration, 2024)
The paper focuses on the role of innovation ecosystems in renewing the environment for small and medium-sized businesses and public administration in Ukraine. The aim of the article is to critically synthesize current theoretical research on the role of innovation ecosystems and develop proposals for their use as a potential driver of Ukrainian small and medium-sized businesses in wartime and post-war periods. The article provides a concise literature review to identify and analyse relevant literature on the connections and opportunities between digital age requirements and current strategies of associative and non-associative business structures. The review will be conducted considering digital transformation and the further acceleration of digitalization under martial law in Ukraine and in the context of the recent Covid-19 pandemic crisis. An important conclusion is drawn that the development of innovation ecosystems in Ukraine can lead to the creation of new high-tech clusters, especially in the IT sector, biotechnology, agrotechnology, and renewable energy. Prospects for further research are related to studying and substantiating the business ecosystem format for Ukraine. The business ecosystem format can play a key role in the recovery and development of Ukraine’s economy, especially in the context of supporting small and medium-sized enterprises (SMEs) during the war and in the post-war period. There are already existing preconditions and a global trend for this.